First principles description of the electronic properties of doped ZnO. Issue 10 (5th August 2013) - Catellani, Alessandra; Ruini, Alice; Cicero, Giancarlo; Calzolari, Arrigo
<x xml:space="preserve">Abstract</x> We here review how the most common intrinsic defects and dopants modify the electronic properties of ZnO, providing novel results obtained by means of accurate first principles density functional calculations. In particular, we show that interstitial H is responsible for the residual and hardly eliminable n‐type character of real ZnO samples. We also show the effects of controlled doping with metal ions to obtain both transparent conductive oxides (Al, Ga, In) and p‐type materials (Ag). We demonstrate that Ag inclusions can be linked to the presence of deep acceptors in the host band gap that may cancel the p‐type character in Ag‐doped ZnO. <inline-graphic xlink:href="ark:/27927/pgg3jzfxvxc" content-type="pssb201200967-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />